1994
DOI: 10.1063/1.468304
|View full text |Cite
|
Sign up to set email alerts
|

The percolation-to-cluster transition during spinodal decomposition of an off-critical polymer mixture. Observation by light scattering and optical microscopy

Abstract: Direct observation of the percolation-to-cluster transition of an off-critical mixture of polybutadiene and polyisoprene was achieved by optical microscopy. According to optical evidence, the transition occurs in a slow and a fast step not revealed in parallel light scattering experiments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
53
2

Year Published

1995
1995
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(60 citation statements)
references
References 5 publications
5
53
2
Order By: Relevance
“…[25,36,48] It is therefore remarkable that spinodal structures with unequal phase fractions are known to disintegrate during coarsening. [49,50] For NPG this implies that networks with low ϕ may exhibit a reduced connectivity density of their load-bearing paths, which would make them anomalously weak and compliant.…”
Section: Role Of Network Connectivity?mentioning
confidence: 99%
“…[25,36,48] It is therefore remarkable that spinodal structures with unequal phase fractions are known to disintegrate during coarsening. [49,50] For NPG this implies that networks with low ϕ may exhibit a reduced connectivity density of their load-bearing paths, which would make them anomalously weak and compliant.…”
Section: Role Of Network Connectivity?mentioning
confidence: 99%
“…gravity). Polymer blends in which pinning has recently been observed for offcritical composition include X-7G/poly(ethylene teraphthalate) (a liquid crystalline polymer/homopolymer blend) [1], poly(styrene-ran-butadiene)/polybutadiene [4], poly(styreneran-butadiene)/polyisoprene [4], and polybutadiene/polyisoprene [6].…”
Section: Introductionmentioning
confidence: 99%
“…Experiments on spinodal decomposition in polymer blends show that the coarsening process may sometimes slow dramatically or even cease before reaching equilibrium [1] - [6]. In these systems, spinodal decomposition -which is the process by which a thermodynamically unstable mixture demixes to a stable, phase-separated equilibrium state [7] - [13] -proceeds normally for some time following a quench to the unstable region (T < T s ), and then stops.…”
Section: Introductionmentioning
confidence: 99%
“…The percolating, bicontinuous phase structure originating in spinodal decomposition is generally said to develop rapidly by hydrodynamic coarsening, in cases where the characteristic length of the structure develops linearly with time. 17 In the TPE/oil system, hydrodynamic flow may be the major mechanism of structurecoarsening in the initial stage at which D ∝ t. Now we consider the late stage, where D ∝ t 1/3 . Figure 8 shows the optical micrographs of phase separation in a very late stage at 60 • C. The coarsening process is easily observed, since it proceeds slowly at around the 70 min after the onset of phase separation.…”
Section: Alteration Of Time-evolution Of Phase Separationmentioning
confidence: 99%
“…The study also proposed that such pinning might originate in a kinetic barrier that suppresses the diffusion of polymer-molecules. After the initial report of Hashimoto, Gronski et al 17 studied the PC transition by optical micrographs, as well as light scattering. They observed that the morphology evolves from a percolating structure to clusters of a globular shape of a minority component around the time at which the PC transition is detected by light scattering.…”
Section: Alteration Of Time-evolution Of Phase Separationmentioning
confidence: 99%